Apresentação das entrevistas aos Mestres Pedro Correia e Pedro de Lima - Federico Sanguinetti; Ranah Duarte; Gláucio Teixeira; Daniel Fernandes; Itaiara Iza Simplício da Silva; Valdicley Euflasino da Silva; Raquel Cardozo da Silva (Perspectiva Filosófica)
Apresentação das entrevistas aos Mestres Pedro Correia e Pedro de Lima.